2016
DOI: 10.1016/j.polymdegradstab.2015.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E-stabilised UHMWPE for surgical orthopaedic implants: Quantification of vitamin E and characterisation of its transformation products

Abstract: The fate of vitamin E and the formation and identification of its transformation products were investigated at different stages of the manufacturing process of commercially produced cross-linked (by γ-irradiation) UHMWPE stabilised with vitamin E (vitamin E infused-post irradiation) used for tibia-components (as articulating surfaces) in total knee arthroplasty (total knee replacement). Vitamin E (α-tocopherol) and its transformation products were extracted from microtomed Tibia films and the different product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Therefore, some may not view this trend as universally applicable to every irradiated UHMWPE/Vitamin E blend material. For example, Doudin and Al‐Malaika reported 84% of Vitamin E introduced by a soaking method was extractable after a 25 kGy sterilization dose . These authors also identified and quantified various Vitamin E photochemical transformation products.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, some may not view this trend as universally applicable to every irradiated UHMWPE/Vitamin E blend material. For example, Doudin and Al‐Malaika reported 84% of Vitamin E introduced by a soaking method was extractable after a 25 kGy sterilization dose . These authors also identified and quantified various Vitamin E photochemical transformation products.…”
Section: Discussionmentioning
confidence: 99%
“…As described in Supporting Information, Figs. S3 and S4, we made a screening‐level estimation of the maximum amount of total ungrafted photoproducts present after irradiation based on a simple reaction model powered by the available literature data of Doudin and Al‐Malaika . For an initial loading of 0.1 wt % Vitamin E in UHMWPE, our analysis suggests at most 0.01 wt % of an individual transformation product (trimers) could be formed by irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations